Mechanistic insight into the roles of anions and cations in the degradation of poly(ethylene terephthalate) catalyzed by ionic liquids. Issue 34 (18th August 2021) - Ju, Zhaoyang; Zhou, Lei; Lu, Xingmei; Li, Yao; Yao, Xiaoqian; Cheng, Shenyu; Chen, Gangwei; Ge, Chengsheng
Abstract : The effects of anions and cations in ILs on the degradation of PET have been studied, and a mechanism has been proposed using DFT calculations and experiments. Abstract : Ionic liquids (ILs) have shown high catalytic activity in the degradation of poly(ethylene terephthalate) (PET), but the effects of the anions and cations, as well as the mechanism, remain ambiguous. Glycolysis is an important recycling method that converts waste PET into monomers through various chemical reactions. To reveal the role of ILs and the molecular mechanism of the glycolysis of PET, density functional theory (DFT) calculations have been carried out for the possible pathways for the generation of bis(hydroxyethyl)terephthalate (BHET) catalyzed by isolated anions/cations and ion pairs at different sites. The pathway with the lowest barrier for the glycolysis of PET is the cleavage of the C–O ester bond, which generates the BHET monomer. The synergistic effects of the cations and anions play a critical role in the glycolysis of PET. The cations mainly attack the carbonyl oxygen of PET to catalyze the reaction, and the anions mainly form strong H-bonds with PET and ethylene glycol (EG). In terms of the mechanism, the H-bonds render the hydroxyl oxygen of EG more electronegative. The cation coordinates the carbonyl oxygen of the ester, and the hydroxyl oxygen of EG attacks the ester group carbon of PET, with proton transfer to the carbonyl oxygen. A four-membered-ring transition state would be formed by PET, EG, and the IL catalyst, which regularly accelerates the degradation of PET. These results provide fundamental help in understanding the roles of ILs and the mechanism of IL-catalyzed PET degradation.